A Parish Pastor's View of Evangelical Lutheran Worship - Purdum, Elizabeth (Dialog, 2008)
Introducing ELW has been an adventure with many highlights and a few disappointments. This congregation still prints everything in a bulletin, but notes that ELW gives a congregation freedom to use alternatives in the liturgy. ELW will be useful for years to come.